The trials of Muhammad Ali [videorecording (DVD)] - Siegel, Bill; Siegel, Bill; Ali, Muhammad, 1942-2016; Ali, Rahaman, 1940-; Farrakhan, Louis; X, Malcolm, 1925-1965; Elijah Muhammad, 1897-1975 (2013)
Investigates its extraordinary and often complex subject's life outside the boxing ring. From joining the controversial Nation of Islam and changing his name from Cassius Clay to Muhammad Ali, to his refusal to serve in the Vietnam War in the name of protesting racial inequality, to his global humanitarian work, Muhammad Ali remains an inspiring and controversial figure.